(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
This research, first, aims to bring to light the preponderant role that the World Economic Forum played in the late 1970s in the global dissemination of the concept of “competitiveness”. At the same time, it shows that from the beginning, for the World Economic Forum, the premise of “productivity” will lay the foundations for a reflexive, managerial and economic way of thinking, which will focus on the advantage of competitors. In other words, this seeks to think of the historical, quantitative ideas of productivity and “business growth” as the starting point of competitiveness. As a result, secondly, it will be explained that, particularly since the 1980s, the emphasis placed on growth will become more complex in the field of strategic management in terms of “competitive strengthening”. The strengthening of competitiveness itself will include qualitative dimensions and an integral strategic vision to think offensively and defensively not only about the management of enterprises, but also, therefore, about the economy of nations. Thus, this research sociologically problematises the contemporary notion of “competitiveness” and does so by highlighting the actors, discourses, and central reconfigurations of the concept in its historical development.